2007
DOI: 10.1117/12.735832
|View full text |Cite
|
Sign up to set email alerts
|

Mounting and alignment of full-shell replicated x-ray optics

Abstract: We are developing grazing-incidence x-ray optics for astronomy. The optics are full-cylinder mirror shells fabricated using electroformed-nickel replication off super-polished mandrels. For space-based applications where weight is at a premium, very-thin-walled, light-weight mirrors are required. Such shells have been fabricated at MSFC with < 15 arcsec resolution. The challenge, however, is to preserve this resolution during mounting and assembly. We present here a status report on a mounting and alignment sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The picture of the alignment and mounting station with a 230 mm diameter shell installed is shown in figure 2. The design considerations for the station were discussed in a previous paper 5 . It was shown that mirror shell distortions due to tilt and support point displacements can be determined using shell circularity measurements carried out close to the shell edges.…”
Section: Shell Alignment and Mounting Stationmentioning
confidence: 99%
“…The picture of the alignment and mounting station with a 230 mm diameter shell installed is shown in figure 2. The design considerations for the station were discussed in a previous paper 5 . It was shown that mirror shell distortions due to tilt and support point displacements can be determined using shell circularity measurements carried out close to the shell edges.…”
Section: Shell Alignment and Mounting Stationmentioning
confidence: 99%